MENGGUGAT KEBEBASAN INDIVIDU DALAM PENEGAKAN UU ITE PERSPEKTIF EKSISTENSIALISME JEAN PAUL SARTRE - Noorzeha, Fuad; Kafaabillah, Dita; Suryosumunar, John Abraham Ziswan (Prodi Hukum Agama Hindu Jurusan Dharma Sastra IAHN Gde Pudja Mataram, 2022)
In Indonesia, human freedom is fostered through the democratic concept of Pancasila. However, sometimes human freedom with democracy still cannot be realized freely, because this freedom for some people is limited by Law No. 11 of 2008 concerning electronic information and transactions or commonly referred to as the ITE Law. The reason is, the ITE Law seems to regulate human freedom in the use of information media and electronic technology which should provide freedom and encourage the development and progress of information. Supposedly, the function and establishment of the law are to solve the problem of cybercrime Cybercrime. However, the law is instead used to restrict everyone's freedom of opinion, argument, and opinion. According to Satre freedom for humans in an authentic form capable of being responsible for what is done. That is, freedom for the Sastre is the essence of man so that man can choose what he should do without the need for subjective limitations. The purpose of this paper is to define human freedom in the ITE Law through Sartre's existentialism. This research is library research with qualitative methods. This research is considered important to guide that the ITE law restricts human existential freedom. Di Indonesia kebebasan individu dibina melalui konsep demokrasi Pancasila. Namun, terkadang kebebasan individu melalui prinsip demokrasi di Indonesia masih belum terealisasikan secara adil. Pasalnya, UU ITE seolah-olah mengatur kebebasan individu dalam penggunaan media informasi dan teknologi elektronik serta menyelesaikan permasalahan kejahatan dunia maya Cyber crime. Akan tetapi, di sisi lain UU justru digunakan untuk membatasi kebebasan setiap orang untuk berpendapat, berargument, beropini. Menurut Satre kebebasan bagi manusia dalam bentuk otentik yang mampu bertanggungjawab atas apa yang diperbuat. Artinya, kebebasan bagi Sastre merupakan esensi manusia sehingga manusia dapat memilih apa yang seharusnya dia lakukan tanpa perlu Batasan secara subjektif. Tujuan dari penulisan ini adalah mengartikan kebebasan individu di dalam UU ITE melalui kaca mata eksistensialisme Sartre. Penelitian ini merupakan penelitian pustaka (library research) dengan metode kualitatif. penelitian ini dianggap penting untuk memberikan panekanan bahwa seharusnya penegakkan hukum UU ITE tidak membatasi kebebasan eksistensial manusia.